2022
DOI: 10.1021/acs.jced.2c00549
|View full text |Cite
|
Sign up to set email alerts
|

Solution Thermodynamic Properties of {Tetrabutyl Ammonium Bromide:Glycerol} Hydrophilic DESs at T = 298.15–348.15 K and 0.1 MPa and an Approach over Solvent Extraction of Cr(VI) Using {Tetrabutyl Ammonium Bromide:Decanoic Acid/Oleic Acid} Hydrophobic DESs

Abstract: This study focuses on determining a pseudo-binary mixture's volumetric properties between 298.15 and 348.15 K temperature over the whole mole fractions to understand the molecular interaction between aqueous chromium solution and hydrophilic deep eutectic solvents (DESs). The solution thermodynamic properties like the mixtures' excess molar volume, partial molar volume and excess partial molar volume of individual components in the solution, apparent molar volume, partial molar volume at infinite dilutions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Learning the functional groups and strength of H-bonding interactions involved in the hydrogen bond acceptor (HBA) and hydrogen bond donors (HBDs) is essential. Our previous research article reported the FTIR spectra of all synthesized DESs using glycerol, capric acid, and oleic acid with TBAB …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning the functional groups and strength of H-bonding interactions involved in the hydrogen bond acceptor (HBA) and hydrogen bond donors (HBDs) is essential. Our previous research article reported the FTIR spectra of all synthesized DESs using glycerol, capric acid, and oleic acid with TBAB …”
Section: Resultsmentioning
confidence: 99%
“…Our previous research article reported the FTIR spectra of all synthesized DESs using glycerol, capric acid, and oleic acid with TBAB. 39 4.2.1. FTIR Spectra of HBA and HBDs Used in This Study.…”
Section: Ftir Inferencesmentioning
confidence: 99%